ANALISIS YURIDIS TERHADAP PEMBERIAN GRASI BAGI TERPIDANA MATI KASUS NARKOBA DI INDONESIA - Dedek Budi Saputra; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The narcotics crime shows the development of increasingly rapid. It is just not the very poor condition of wearer but also the industry as a dark against narcotic drugs and psychotropic substances is thus the largest in the world is done in Indonesia. The government of Indonesia has also issued the law containing the criminal threat is dead against the narcotics crime, that is Act. No.35 of 2009 on Narcotics. When linked with the death penalty, the row inmates are entitled to propose a efforts law. The efforts of law include an appeal, cassation and judicial review. In addition, the convicted person can apply for clemency to the President.The purpose of this study to know the procedure for granting clemency death convicted of narcotics based on Act Number 5 of 2010 concerning Amendment to Law Number 22Year 2002 on clemency and to know the basic consideration of the President in granting Pardons to convicted of drug cases.The research was done by using a normative approach, namely the principles of law, the type of data in this research his to use primary legal materials of the Constitution ofthe Republic of Indonesia Year 1945, and the Act, secondary legal materials (books relating to results research that is granting pardons to convicted narcotics and the data from the internet) and tertiary legal materials (Dictionary of Indonesian Language), data collection techniques in this study with the study of Librarianship and data analysis using the deductive method is a way of drawing conclusions from the proposition that general to the specific.From the research problem, there are two main things that can be inferred. First, against a court ruling which has acquired permanent legal force, the convicted person can apply for clemency to the President. A court ruling may be filed a petition for clemency was the verdict of the criminal to death, life imprisonment at most 2 years low. A period of filing of pardons is one years since the court ruling abtained legal power anyway. Second, the President may grant clemency to provide basic reason juridical considerations clearly, firmly and accountable as well as taking into consideration the relevant agencies.Keywords: Granting-Death Convicted-Narcotics